2019
DOI: 10.1002/jmri.26766
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning enables automatic detection and segmentation of brain metastases on multisequence MRI

Abstract: Background: Detecting and segmenting brain metastases is a tedious and time-consuming task for many radiologists, particularly with the growing use of multisequence 3D imaging. Purpose: To demonstrate automated detection and segmentation of brain metastases on multisequence MRI using a deep-learning approach based on a fully convolution neural network (CNN). Study Type: Retrospective. Population: In all, 156 patients with brain metastases from several primary cancers were included. Field Strength: 1.5T and 3T.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
168
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(194 citation statements)
references
References 34 publications
13
168
1
Order By: Relevance
“…Although brain metastases are usually well-circumscribed contrast-enhancing lesions, the manual, three-dimensional segmentation is time-consuming. To overcome this issue, machine learning techniques are being developed for the automated detection and segmentation of brain metastases using deep learning (31,32). However, these tools still have to prove their reliability and added value to ultimately become part of clinical routine.…”
Section: Segmentationmentioning
confidence: 99%
“…Although brain metastases are usually well-circumscribed contrast-enhancing lesions, the manual, three-dimensional segmentation is time-consuming. To overcome this issue, machine learning techniques are being developed for the automated detection and segmentation of brain metastases using deep learning (31,32). However, these tools still have to prove their reliability and added value to ultimately become part of clinical routine.…”
Section: Segmentationmentioning
confidence: 99%
“…The first application which produced state-of-the-art results in automated segmentation of BM in MRI was published in 2015 by Losch et al [5]. Since then, a large variety of network architectures for deep learning including GoogLeNet [6], CropNet [7], DeepMedic [8] and En-DeepMedic [9] have been tested. A common limitation is the high number of false positives and the small sample sizes used for training.…”
Section: Introductionmentioning
confidence: 99%
“…The system yielded an average Dice similarity coefficient of 0.67, where the detection false-positive rate in connection to the sensitivity percentage is not reported. More recently, Grøvik et al [15] demonstrated the usage of 2.5D fully CNN, based on GoogLeNet architecture [16], for detection and segmentation of BM. Their solution utilized multiple sequences of MRI for each patient: T1-weighted 3D fast spin-echo (CUBE), post-contrast T1-weighted 3D axial IR-prepped FSPGR, and 3D CUBE fluid-attenuated inversion recovery.…”
mentioning
confidence: 99%